2016
DOI: 10.14744/anatoljcardiol.2016.6706
|View full text |Cite
|
Sign up to set email alerts
|

Aortic flow propagation velocity, epicardial fat thickness, and osteoprotegerin level to predict subclinical atherosclerosis in patients with nonalcoholic fatty liver disease

Abstract: Objective:Nonalcoholic fatty liver disease is the most common cause of liver dysfunction in Western countries and an independent risk factor for atherosclerotic heart disease. Appropriate noninvasive parameters are lacking for optimal risk stratification of cardiovascular disease in these patients. We evaluated several recently discovered noninvasive parameters for atherosclerosis in patients with nonalcoholic fatty liver disease: epicardial fat thickness, aortic flow propagation velocity, and osteoprotegerin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, NAFLD leads to significant changes in vessel functionality. A study by Oguz et al (41) showed that patients with NAFLD had a significantly lower aortic flow propagation velocity. Another study demonstrated that coronary flow velocity reserve is significantly impaired in patients with NAFLD (42,43).…”
Section: Cardiovascular Disordersmentioning
confidence: 99%
“…Furthermore, NAFLD leads to significant changes in vessel functionality. A study by Oguz et al (41) showed that patients with NAFLD had a significantly lower aortic flow propagation velocity. Another study demonstrated that coronary flow velocity reserve is significantly impaired in patients with NAFLD (42,43).…”
Section: Cardiovascular Disordersmentioning
confidence: 99%
“…Several articles described a significant association between EFT and NAFLD. Oguz et al conducted a cross-sectional study concluding that EFT and osteoprotegerin level were increased while aortic flow propagation velocity was decreased in patients with NAFLD (105). Another study involving 868 subjects from the PLIC Study conducted by Baraghetti et al reported that hepatic steatosis and EFT were related to an increased incidence of extra-cardiac plaques (106).…”
Section: Cardiovascular Disease In Fatty Liver Diseasementioning
confidence: 99%
“…A total of 58 articles were excluded because they did not meet the inclusion criteria. Finally, 18 articles (thirteen cross-sectional studies (Fracanzani et al, 2016[ 7 ]; Brouha et al, 2018[ 3 ]; Cho et al, 2017[ 4 ]; Kim et al, 2016[ 18 ]; Psychari et al, 2016[ 33 ]; Petta et al, 2015[ 32 ]; Granér et al, 2015[ 8 ]; Topuz et al, 2014[ 39 ]; Turan, 2020[ 40 ]; Lai et al, 2012[ 19 ]; Ledda et al, 2021[ 21 ]; Iacobellis et al, 2008[ 15 ]; Meng et al, 2018[ 27 ]) and five case-control studies (Iacobellis et al, 2014[ 12 ], Colak et al, 2012[ 5 ], Yilmaz et al, 2011[ 43 ], Sunbul et al, 2014[ 37 ], Oğuz et al, 2016[ 30 ]), published between 2008 and 2021, which met our inclusion criteria were reviewed. Out of these, fourteen studies measured EAT thickness using echocardio-graphy; in the rest, EAT volume was assessed using CT or MRI methods (Brouha et al, 2018[ 3 ]; Granér et al, 2015[ 8 ]; Ledda et al, 2021[ 21 ]; Meng et al, 2018[ 27 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of studies are shown in the Table 1 (Tab. 1) (References in Table 1: Brouha et al, 2018[ 3 ]; Cho et al, 2017[ 4 ]; Colak et al, 2012[ 5 ]; Fracanzani et al, 2016[ 7 ]; Granér et al, 2014[ 8 ]; Iacobellis et al, 2008[ 15 ]; Iacobellis et al, 2014[ 12 ]; Kim et al, 2016[ 18 ]; Lai et al, 2012[ 19 ]; Ledda et al, 2021[ 21 ]; Meng et al, 2018[ 27 ]; Oğuz et al, 2016[ 30 ]; Petta et al, 2015[ 32 ]; Psychari et al, 2016[ 33 ]; Sunbul et al, 2014[ 37 ]; Topuz et al, 2014[ 39 ]; Turan, 2020[ 40 ]; Yilmaz et al, 2011[ 43 ]).…”
Section: Resultsmentioning
confidence: 99%